2020
DOI: 10.1002/lary.28587
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatric Nutritional Risk Index as a Prognostic Factor in Patients with Advanced Head and Neck Cancer

Abstract: Objective The Geriatric Nutritional Risk Index (GNRI) is a simple and well‐established nutritional assessment tool and is a significant prognostic factor in various cancers. However, the role of the GNRI in predicting clinical outcomes in patients with advanced head and neck cancer (AHNC) has not been investigated. The aim of the present study was to examine the association between the GNRI and prognosis in patients with AHNC. Study Design Retrospective cohort study. Methods Data collected between 2002 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Previous studies have highlighted the usefulness of the GNRI when assessing how physically fit elderly patients are who have chronic diseases [11]. Recent studies have assessed the usefulness of the GNRI in patients with various cancers, including those of the lung, pancreas, head and neck, and gastrointestinal organs [7,[13][14][15][16][17][18]. In this study, we evaluated the potential of three immunonutritional parameters as prognostic factors for second-line PEM treatment in patients with mUC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have highlighted the usefulness of the GNRI when assessing how physically fit elderly patients are who have chronic diseases [11]. Recent studies have assessed the usefulness of the GNRI in patients with various cancers, including those of the lung, pancreas, head and neck, and gastrointestinal organs [7,[13][14][15][16][17][18]. In this study, we evaluated the potential of three immunonutritional parameters as prognostic factors for second-line PEM treatment in patients with mUC.…”
Section: Discussionmentioning
confidence: 99%
“…3 [1][2][3][4][5][6] vs. 6 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in the low-GNRI vs. high-GNRI group). In addition, the median CSS with second-line PEM therapy was 3.6 months (95% confidence interval [CI]: 2.5-6.1) and 11.8 months (95% CI: 6.2-NA) for the low-GNRI and the high-GNRI group, respectively (Fig.…”
Section: Patients' Characteristics and Tumor Responsementioning
confidence: 91%
See 1 more Smart Citation
“…However, studies evaluating young adults have confirmed that GNRI assessment is valuable in the evaluation of the nutritional status in this population (15,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 97%
“…The geriatric nutritional risk index (GNRI), first reported by Bouillanne et al, is a novel and wellestablished objective nutritional assessment tool for the prediction of malnutrition-related risks of mortality and morbidity, including infection and bedsores, in hospitalized older patients (i.e., those aged ≥65 years) [1]. The GNRI consists of two parameters: serum albumin level and body weight; this index has been reported as a prognostic factor in patients with various cancers, such as gastric cancer, hepatocellular carcinoma, and head and neck cancer [2][3][4].…”
Section: Introductionmentioning
confidence: 99%